2019
DOI: 10.1093/aje/kwz065
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Associations Between Disaster Experiences and Cardiometabolic Risk: A Natural Experiment From the 2011 Great East Japan Earthquake and Tsunami

Abstract: We investigated the association between disaster experience and the cardiometabolic risk of survivors 2.5 years after disaster onset, adjusting for health information predating the disaster, using natural experiment data stemming from the 2011 Great East Japan Earthquake and Tsunami. We used data from a cohort of adults aged 65 years or older in Iwanuma City, Japan, located 80 km (128 miles) west of the earthquake epicenter. The baseline survey was completed 7 months before the disaster, and the follow-up surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 36 publications
3
33
1
Order By: Relevance
“…In the city of Iwanuma (in the neighboring prefecture of Miyagi), Shiba et al. found that tsunami-affected survivors showed increased triglyceride levels after relocation to temporary housing [ 9 ]. These are consistent in our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the city of Iwanuma (in the neighboring prefecture of Miyagi), Shiba et al. found that tsunami-affected survivors showed increased triglyceride levels after relocation to temporary housing [ 9 ]. These are consistent in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the deleterious impacts of living in temporary housing on mental health, previous studies have also indicate that this type of accommodation increases the risk for physical health impairments, including deteriorating physical performance [ 6 ], reduced physical activity/sedentarism [ 7 ], deteriorating cognitive function [ 8 ], and increases in body weight [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, changes in BMI between baseline and follow-up were also not associated with the new-onset arthritis. A previous longitudinal study from Japan reported that housing damage after the earthquake and tsunami was associated with obesity ( Shiba et al, 2019 ). Thus, our results were inconsistent with the previous studies that indicated that obesity is a risk factor for arthritis ( Chaganti and Lane, 2011 ; Daïen and Sellam, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these individuals are more likely to suffer from previous injuries, which also increases the risk for subsequent arthritis ( Felson, 1994 ). Moreover, obesity, which is associated with SES ( McLaren, 2007 ; Shiba et al, 2019 ; Wardle et al, 2002 ), has also been reported as a common risk factor for arthritis ( Chaganti and Lane, 2011 ; Daïen and Sellam, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some conflicting findings have also been reported among older population. For example, Shiba, Hikichi, Aida, Kondo, and Kawachi (2019) used a longitudinal natural experiment data from the 2011 Great East Japan Earthquake and Tsunami, reporting that older survivors (65 years or older) who experienced housing damage showed a 4.36-mmHg decrease in DBP after 2.5 years (95% CI = −8.67, −0.06), but no significant change in SBP, compared with those with no housing damage. Similarly, Ebner, Ohsawa, Igari, Harada, and Koizumi (2016) found that among those evacuated after the Fukushima Daiichi nuclear power plant disaster (mean age = 68.3 years as of 2013), there was a decrease of both SBP and DBP after 2 years, compared to that obtained before the disaster, in spite of the increase in other chronic conditions (e.g., metabolic syndrome, diabetes, dyslipidemia, hyperuricemia, and chronic kidney disease).…”
Section: Introductionmentioning
confidence: 99%